Familial Kidney Disease Phenocopying Hypertensive Nephropathy - Özdemır, Fezile; Oygar, Duriye Deren; Behlul, Ahmet; Ataç, Salahi; Bardak, Simge; Yükseliş, Meral; Papagregoriou, Gregory N. (S. Karger AG, 2025)
Abstract – Introduction: Familial kidney disease is common in Cyprus and previous studies have found that the majority of families have mutations in Alport syndrome genes COL4A3/4/5. We have collected data from over 50 Turkish Cypriot families in whom kidney disease appears to follow an autosomal dominant pattern, and looked for pathological variants in these genes. Methods: Probands from 55 families underwent massive parallel DNA sequencing using a glomerular gene panel for familial hematuria, and whole-exome sequencing (WES) was also performed in 22 of them. Clinical records were reviewed. Results: Likely pathogenic variants were identified in 7 of the 55 families (COL4A3 [3], COL4A4 [2], and COL4A5 [2]), leaving 48 unsolved families. Among the latter a common missense variant of uncertain significance (COL4A4:p.G545A), was present in 5 families (9.1%). In contrast to families with a pathogenic variant in COL4A3/4 and a clear glomerular phenotype the 5 families (54 patients with clinical and genetic data), manifested near dominant susceptibility with incomplete penetrance, presenting with hypertension, variable and intermittent microscopic hematuria, and minimal proteinuria, <1 g/day until the estimated glomerular filtration rate (eGFR) fell below 30 mL/min, after which it increased in some individuals. Of those over age 50, 20% had reached end-stage by median age of 66 (48–80) years. Conclusions: We describe a kidney disease with mild hypertension that is more characteristic of a tubulointerstitial disease and phenocopies hypertensive nephropathy. While the variant COL4A4:p.G545A is not responsible for a Mendelian CKD phenotype, it appears to increases the susceptibility, acting as a hypomorphic variant contributing to Alport spectrum nephropathy. Early detection and treatment with ACE inhibitors should prolong kidney survival to an age where hemodialysis is avoided. © 2025 S. Karger AG, Basel
Keywords: Alport syndrome; Autosomal dominant; COL4A4; Hypertensive nephropathy; Tubulointerstitial disease